Five Factor Narcissism and threat to fundamental needs following social exclusion engendered by the Cyberball game. (1st January 2021) - Mazinani, Zahra; Shakiba, Shima; Pourshahbaz, Abbas; Vahedi, Mohsen
Abstract: The present study aimed to examine whether the five factor narcissism sub-scales predict a threat to primary needs and mood reactivity in two immediate and delayed stages following social exclusion. The Cyberball, a socially aversive task, was administered in a community sample (n = 307). Participants then filled out the Five Factor Narcissism Inventory-Long Form and The Need Threat Scale at both reflexive and reflective stages. Results indicated that the social exclusion condition uniquely predicts the overall threat to fundamental needs as well as mood reactivity. Vulnerability and neuroticism were predictive of more negative outcomes following social exclusion. Indeed, the needs threat was persistent in participants with higher Neuroticism. Antagonism was associated with more negative affect generally; this pattern was also evident following inclusion. Participants with Grandiosity or Extraversion traits appeared to be unconcerned about this socially painful experience. Additionally, it is indicated that the need to belong and control are significantly more threatened than self-esteem or meaningful existence. In conclusion, it seems evident that vulnerability and neuroticism are determinant variables in predicting negative outcomes of social exclusion in the realm of narcissism. Highlights: Social exclusion predicts increased needs threat and negative affect in Iran. The need to belong and control are most threatened among Iranians. Vulnerability and Neuroticism predict negative outcomes following social exclusion. Needs threats are persistent for participants higher in Neuroticism. Grandiosity, Antagonism and Extraversion do not predict post-Cyberball variables.